Effects of Nodal Distance on Conditioned Stimulus Valences Across Time - Amd, Micah; Machado, Armando; de Oliveira, Marlon Alexandre; Passarelli, Denise Aparecida; De Rose, Julio C. (Frontiers in Psychology, 2019)
A meaningless symbol that repeatedly co-occurs with emotionally salient faces (US) can transform into a valenced symbol (CS). US-to-CS valence transformations have been observed for CS that have been directly (US>CS0) and indirectly (US>CS0>CS1>CS2) linked with face US. The structure of a US>CS0>CS1>CS2 series may be conceptualized in terms of ‘nodal distance’, where CS0, CS1 and CS2 are 0, 1 and 2 nodes from the US respectively. Increasing nodal distance between an evaluated CS and it’s linked US can reduce magnitude of observed CS valence transformations. We explored currently whether nodal distance can influence CS valence extinction, which describes reductions in CS valence following repeated exposures to CS without any accompanying US. In our study, faces with happy/neutral/sad expressions (US) were directly linked with nonsense words (US>CS0). The directly linked CS0 were concurrently linked with other words (CS0>CS1, CS1>CS2). Subjects evaluated all stimuli before and after conditioning, then continued to provide CS evaluations twice a week for six weeks. Bayesian factors provided credible evidence for the transformation and extinction of CS valences that were 0 and 1 nodes from US (all BF10’s > 100). The variability across post-conditioning CS evaluations provides indirect evidence for context-sensitive/propositional and structural/associative operations during CS evaluations.